Cross Border M&A’s in ASEAN and India: A Comparative Critique - TIWARI, Avin; SHUKLA, Gaurav; PANDEY, Suesh Kumar (Journal of Advanced Research in Law and Economics; Vol 11 No 2 (2020): JARLE Volume XI Issue 2(48) Spring 2020, 2020)
Cross-border merger and acquisitions (hereinafter, M&A’s) have increased exponentially in Asia since the mid-1990s due to the liberalization of the economy, the deregulation of the service sector, privatization of state-owned public enterprises, and the relaxation of regulatory controls over cross-border M&A's. ASEAN economies and India are significant players in the global arena for cross-border M&A's, and thus, their importance cannot be undermined. Cross-border M&A's have distinctive implications on the socio-economic scenario of a Nation, and most importantly, it impacts substantial change in legal dimensions, involving compliance requirements, acquisition procedures, and tax liabilities. The present study is a doctrinal one; the primary objective being, a legislative frame analysis of select ASEAN countries and India with regards to cross-border M&A’s. The top five ASEAN countries, viz., Indonesia, Malaysia, the Philippines, Singapore, and Thailand were selected on account of the cross-border trade volume over the past decade. The authors applied comparative and analytical methods to pursue the research inquiry. The second objective was to ascertain the vital macro-economic factors playing a decisive role in the outcome of cross-border M&A’s in the select region. Here the authors highlighted the relationship between certain macro-economic factors like trade openness, financial integration, increased inflation, increased GDP, etc. which positively impact M&As. The third and final objective was to analyze the trends of cross border M&A’s in the select region for the past decade, i.e. 2008 to 2018, as this period perfectly encapsulates a complete economic cycle from depression to boom alongside major legal developments in the field of cross-border M&A’s around the world. Furthermore, while undergoing the study, the authors highlighted certain risk factors in terms of competition, transaction, and people with regards to cross border M&A’s in the select region. Findings from the study indicated that ASEAN economies have little experience in framing and enforcing competition policies, hence, a suitable policy to reduce risk is the immediate need of the hour.